Cockfights and Colonial Ghosts: Identity and Violence in Latin American Postcolonial Horror - Britanico, King Philip (International Journal of Language and Literary Studies, 2025)
This paper analyzes Cockfight by María Fernanda Ampuero through a postcolonial lens, focusing on identity fragmentation and cultural dislocation as shaped by historical trauma and colonial legacies. Using Homi Bhabha's concepts of "cultural hybridity" and the "Third Space," the study reveals how Ampuero's short stories explore gendered violence, familial horror, and psychological trauma within postcolonial Ecuador. Through horror motifs, the narratives depict women navigating oppressive domestic spaces and confronting hybrid identities shaped by the clash between colonial structures and indigenous traditions. Stories such as Auction and Monsters illustrate how violence is embedded in cultural memory, while Griselda and Blinds expose the lingering effects of colonial exploitation on identity and autonomy. Ampuero's use of horror not only subverts patriarchal and religious norms but also foregrounds the resilience of her female characters, making Cockfight a critical contribution to contemporary Latin American postcolonial literature and demonstrates the enduring relevance of postcolonial frameworks in analyzing contemporary literary expressions of trauma.